Criminal Law Enforcement to Combat Social Media-Based Prostitution - Fuadi Isnawan; Isnawan, Fuadi (KRTHA BHAYANGKARA, 2024)
In Indonesia, social media's pervasive influence has led to the emergence of online prostitution, presenting complex challenges for law enforcement and criminal justice. Unlike traditional forms, online prostitution operates discreetly on digital platforms, complicating regulation and enforcement efforts. The research in this article uses normative legal research methods.  This research examines the socio-cultural, legal, and technological dimensions of this phenomenon, assessing the adequacy of existing legal frameworks and the efficacy of cyberpatrol units in addressing it. Insights aim to inform policy and law enforcement strategies to combat social media-based online prostitution effectively. The result of this research is the intersection of online prostitution and social media platforms presents a complex interplay between technology, commerce, and societal norms within digital environments. Leveraging the communicative potential of social media, individuals discreetly engage in commercial sex work, navigating a dynamic ecosystem that transcends geographical boundaries to create a global marketplace for commercial sexual services. Multimedia elements and specialized terminology tailored to the online sex industry augment the visibility of commercial sexual offerings and facilitate transactional negotiations. However, regulatory frameworks have not effectively addressed the challenges posed by online prostitution, creating a legal vacuum that hinders comprehensive law enforcement. This underscores the critical role of law enforcement agencies, such as the Cyber Police, in combating illicit activities in the digital sphere. By adopting a proactive and data-driven approach informed by social media analytics, law enforcement agencies can optimize their surveillance and intervention strategies to effectively combat online prostitution, safeguard vulnerable individuals, and uphold the integrity of digital platforms. Through continuous collaboration, capacity building, and innovative strategies, law enforcement agencies can mitigate the proliferation of cyber threats and ensure the safety and security of digital communities.